THE USE OF FLASHCARDS AND ITS EFFECTIVENESS IN ELT: A SYSTEMATIC REVIEW - Siska Sari; Ika Intan Nurul Wahidah, Sintia Wati, Della Fadiana, Naf’an Tarihoran (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Flashcards are one of the tools used as a learning medium. Many school teachers have used flashcards as a medium for learning English. This article aims to conduct a systematic review of using flashcard to enhance proficiency in English Language Teaching (ELT). Using the PRISMA method, this article analyzed various previous studies relevant to the topic. The search strategy is based on the following keywords: "flashcard" "English" "elementary school" and "primary school" with 3 data from Mendeley, Eric, and Google Scholar. Based on the results of this article, 2315 articles were found, which later 14 articles used in the final analysis became. The use of flashcards in English learning in elementary schools shows that flashcard help students learn words more effectively. Various studies show that the use of traditional and digital flashcards significantly increases students' understanding and motivation to learn. The integration of technologies such as digital flashcards and augmented reality also increases the effectiveness of flashcard learning. Thus, the use of flashcards can be considered an innovative and effective learning strategy to improve students' English skills at the elementary school level.